The National Registry of Recidivism, Identification and Criminal Statistics - Urgently creation - Bard, Leopoldo (1926)
It has enacted a penal code, which legislates on recidivism across the country, and not only that, but also want the new code for the purposes of accountability and the suspended sentence, taking into account all background on the personality of the offender.